2019
DOI: 10.1051/matecconf/201925802004
|View full text |Cite
|
Sign up to set email alerts
|

Informal housing construction workers’ perceptions toward the improvement of effective leadership and performance

Abstract: Practically, as other construction projects, the workforce in housing construction projects is still dominated by informal workers who belong to a group and controlled by a leader. Accordingly, developer companies consider that informal worker leaders play an important role in improving the informal workers’ performance in housing construction projects. Therefore, the purpose of this study is to explore the effective leadership style that can improve the performance of informal workers in housing construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The similarity of informal workers' situation and economic patterns in developing countries (Lukiyanto, 2018;Mehrotra, 2009;Wijayaningtyas & Lukiyanto, 2019). This study's results may also be used as a reference for solving the same problem in other developing countries.Literature Reviews Informal workers are not economically secure; therefore, they are very vulnerable to an economic decline (Mehrotra, 2009;Wijayaningtyas & Lukiyanto, 2019). They generally work only by relying on physical strength, so they get paid when they work.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The similarity of informal workers' situation and economic patterns in developing countries (Lukiyanto, 2018;Mehrotra, 2009;Wijayaningtyas & Lukiyanto, 2019). This study's results may also be used as a reference for solving the same problem in other developing countries.Literature Reviews Informal workers are not economically secure; therefore, they are very vulnerable to an economic decline (Mehrotra, 2009;Wijayaningtyas & Lukiyanto, 2019). They generally work only by relying on physical strength, so they get paid when they work.…”
Section: Introductionmentioning
confidence: 71%
“…Informal workers are not economically secure; therefore, they are very vulnerable to an economic decline ( Mehrotra, 2009 ; Wijayaningtyas and Lukiyanto, 2019 ). They generally work only by relying on physical strength, so they get paid when they work.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level residential housing workers in Indonesia are seasonal workers from the countryside who work on construction projects for a set period of time, similar to general construction workers. Several previous studies have revealed the situation of informal construction workers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is one of the countries currently developing rapidly and experiencing the development process in the construction world, such as housing, industry, offices, commercial, property, etc [1]. The number of Indonesians who occupy a large number of people in the world is one of the causes of the increase in construction development at this time [2].…”
Section: Introductionmentioning
confidence: 99%